Young People’s Struggle for Recognition: The Movement of la Lupa and School Occupations - Galiano, Angelo (Italian Sociological Review, 2026)
This article examines some of the social and political aspects resulting from the action of young people during the pandemic, through the description and analysis of a specific performance of conflict, occupation. Between October 2021 and March 2022 an unprecedented wave of keenly-felt student demonstrations swept through Italy, triggered by the occupation of several schools in Rome. The article is based on a quali-quantitative methodology. The chronology of the protest was reconstructed by means of an analysis of the national and local daily press.